GARP and GARP-Treated tDC Prevented the Formation of Atherosclerotic Plaques in ApoE−/- Mice - Cai Y; Zeng Q; Liu Y; Zhu R; Yu K; Xu W; Wang Y; Ding Y; Yu J; Pan C; Peng Y; Mao Y; et al. (Dove Medical Press, 2021)
Yifan Cai,1 Qiutang Zeng,1 Yuzhou Liu,2 Ruirui Zhu,1 Kunwu Yu,1 Wenbin Xu,1 Yue Wang,1 Yan Ding,1 Jian Yu,1 Chengliang Pan,1 Yudong Peng,1 Yi Mao,1 Peng Cheng,1 Lun Huang,1 Xiaobo Mao,1 Yucheng Zhong1 1Department of Cardiology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People's Republic of China; 2Department of Cardiology, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, 450052, People's Republic of ChinaCorrespondence: Yucheng ZhongLaboratory of Cardiovascular Immunology, Institute of Cardiology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, 1277 Jie-Fang Avenue, Wuhan, 430022, People's Republic of ChinaTel +86-27-85726423Fax +86-27-85726425Email zyc811029@126.comPurpose: This study aims to clarify the specific mechanism by which GARP affects the atherosclerotic plaques in ApoE−/- mice and the effect of GARP-tDC on atherosclerosis.Methods: The mice were randomly divided into three groups: the control group, the GARP-overexpressed group and the GARP-inhibited group. After 12 weeks, all the mice were euthanized, and the specimens were collected. In vitro, experiments were conducted to observe the effect of GARP on DC phenotype and the changes of the proportion of CD4+CD25+Foxp3+ Treg cells when GARP-tDCs were co-cultured with CD4+ T cells. Furthermore, adoptive transmission of GARP-tDCs was used to observe the effect on atherosclerotic plaque in mice.Results: The GARP-overexpressed group enhanced the biological activity of Foxp3+ CD4+CD25+ Tregs and resulted in increased expression of LAP in T cells. In addition, the GARP-overexpressed group significantly suppressed the function of Th1 and Th17, and decreased the secretion of INF-γ and IL-17A. Thus, GARP had a protective effect on atherosclerosis. In vitro, we found that GARP-tDC had a tolerance-inducing phenotype, and GARP-tDC also had the ability to induce tolerance when co-cultured with CD4+ T cells. More importantly, adoptive transmission of GARP-tDCs reduced the size of atherosclerotic plaques.Conclusion: GARP and the GARP-tDC play protective roles in atherosclerosis. The protective effect of GARP on atherosclerosis is achieved by increasing CD4+CD25+Foxp3+ Treg cells and inhibiting the production of IFN-γ and IL-17A.Keywords: GARP, Foxp3, GARP-tDC, atherosclerosis, LAP